(untitled) (JÓVENES EN LA CIENCIA, 2025)
Artificial intelligence generated content is on the way to solving the problem of the high cost and labor of workflows by producing coherent, human‑like text and graphics, leveraging machine learning models to automate content creation, and enhancing efficiency and scalability. However, ethical concerns, community biases, and misinformation risks necessitate robust guidelines and oversight. Anticipated advances include lowering the entry threshold to generate qualitative content, which underscores the need for responsible governance of services and instruments based on Artificial Intelligence. This article reviews certain existing Artificial Intelligence-based tools that generate different types of content and highlights the ethical and social challenges of their responsible use.